„Nomina actionis” с новыми интернациональными формантами в русском языке эпохи постмодерна (в сопоставлении с польским и чешским языками) - Koriakowcewa, Elena (Wydawnictwo Naukowe UAM, 2010)
The article undertakes to show that in great measure the derivation of neologisms, including nomina abstracta, in Russian and in other Slavic languages links with morphological internalization and “linguistic globalization” processes. Nomina abstracta of Russian, Polish, Czech and other Slavic languages in the situation of the lingual contacting for some time past are used as an illustrative material. Some peculiarities stipulated by the influence of the contacting language are distinguished. This reflects on the lexical composition of international words, international elements of diverse derivative activity, changes in the morphemic structure of nomina abstracta in particular.
“Nomina actionis” with the new international derivative formants in Russian language of postmodern period (in comparison with Polish and Czech language)
„Nomina actionis” z nowymi formantami internacjonalnymi w języku rosyjskim epoki postmoderny (w porównaniu z językiem polskim i czeskim)